Contemporary Russian Substandard - Stěpanova, Ludmila (Bohemica Olomucensia, 2018)
The article describes the history of studying of Russian substandard and the place of substandard in modern Russian speech. The author defines the terms substandard, slang and colloquial speech in Russian linguistic. There are described the largest subject groups of slang names. The author showes the development of slang names and their derivatives. This is demonstrated with contexts from contemporary Russian texts.
Keywords: Contemporary Russian; substandard; slang; colloquial speech; development; derivatives